Neural effects of acupuncture on stroke patients with motor dysfunction: an activation likelihood estimation meta-analysis - Li, Dongxia; Wang, Dongyan; Zhou, Yihao; Zhang, Yuan; Yang, Siyu; Dong, Xu; Cai, Shaojie; Zhang, Ruiting (Frontiers in Neurology, 2024)
Background Functional magnetic resonance imaging has been used in many studies to explore the neural mechanism of acupuncture in patients with post-stroke motor dysfunction. Inconsistent results have been found in these studies, however. This activation likelihood estimation (ALE) meta-analysis was designed to quantitatively integrate changes in brain activity and the neurological effects of acupuncture on patients with motor dysfunction after stroke. Methods We searched PubMed, Embase, Web of Science, the Cochrane Library, China Science and Technology Journal Database, the China Biology Medicine, the China National Knowledge Infrastructure, and Wanfang Data Knowledge Service Platform for literature from the establishment of the database until March 21, 2024. Research papers were selected, data extracted, and quality assessment was done independently by two researchers. The GingerALE software was used for meta-analysis, and Jackknife sensitivity analysis was employed to assess result robustness. Results We ended up analyzing 14 studies that included 235 patients and 100 healthy people. ALE meta-analysis showed that Compared with healthy people, the enhanced brain region in poststroke patients with motor dysfunction was located in the left posterior lobe of the cerebellum, the left inferior frontal gyrus, and the left precuneus (p < 0.001). After acupuncture, the activated regions were mainly located in the left posterior lobe of the cerebellum, the right lentiform nucleus putamen, the right medial frontal gyrus, the right inferior frontal gyrus, the left precuneus, the right middle temporal gyrus, the left claustrum, the left cerebellar tonsil, the right superior marginal gyrus, the inactivated area is located in the right medial frontal gyrus the left precentral gyrus and the right precuneus (p < 0.001). Conclusion Acupuncture can reestablish motor function by causing extensive changes in the brain function of patients with stroke, which may be the neurological effect of acupuncture therapy on stroke patients. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42024526263.